2016
DOI: 10.1002/jnr.23809
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the broad influence of sex hormones and sex differences in the brain

Abstract: Sex hormones act throughout the entire brain of both males and females via both genomic and non-genomic receptors. Sex hormones can act through many cellular and molecular processes that alter structure and function of neural systems and influence behavior as well as providing neuroprotection. Within neurons, sex hormone receptors are found in nuclei and are also located near membranes where they are associated with presynaptic terminals, mitochondria, spine apparatus, post-synaptic densities. Sex hormone rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
315
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 508 publications
(336 citation statements)
references
References 208 publications
(317 reference statements)
13
315
2
6
Order By: Relevance
“…Previous studies have demonstrated that both people suffering from depression and male rats subjected to chronic stress have exhibited hippocampal atrophy . By contrast, female rats showed neuroprotective actions from E2 in the hippocampus, which appeared to spare them from the damage observed in male rats following chronic stress by regulating tropic factors and excitatory neurotransmission to maintain hippocampal activity within an optimal range . Hence, our results suggest that in DOM females E2 treatment improved hippocampal function and enhanced FC with the amygdala, whereas, in SUB females, E2 worked towards the same end, albeit by reducing FC.…”
Section: Discussionmentioning
confidence: 46%
“…Previous studies have demonstrated that both people suffering from depression and male rats subjected to chronic stress have exhibited hippocampal atrophy . By contrast, female rats showed neuroprotective actions from E2 in the hippocampus, which appeared to spare them from the damage observed in male rats following chronic stress by regulating tropic factors and excitatory neurotransmission to maintain hippocampal activity within an optimal range . Hence, our results suggest that in DOM females E2 treatment improved hippocampal function and enhanced FC with the amygdala, whereas, in SUB females, E2 worked towards the same end, albeit by reducing FC.…”
Section: Discussionmentioning
confidence: 46%
“…When studying ovarian hormones, it is important to consider the nature of effects. Broadly, sex hormone effects on the brain and behavior can be organizational or activational . Organizational effects generally concern hormone exposure during sensitive periods of development; they are permanent and have historically been tied to sexual differentiation, in that hormone‐influenced brain circuits persist throughout life and are important for sex‐typed behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that organizational and activational effects of sex steroid hormones play an important role in brain sex differentiation [7,28,29,30,31]. Indeed, neuroprotective actions of estrogen in females underlie sex differences in susceptibility to disorders such as PD and schizophrenia [7,32,33,34], whilst aberrant levels of fetal testosterone have been associated with male preponderance to neurodevelopmental disorders such as autism and ADHD [35,36].…”
Section: Introductionmentioning
confidence: 99%